(- 3/2 + 2/3)^3 : [(- 5/6) : (- 12/5)] =
= (- 9/6 + 4/6)^3: [(- 5/6) * (- 5/12)] =
la divisione diventa moltiplicazione con l'inversa:
[ (- 5/6) * (- 5/12)] = + 25/72 = + ( 5 * 5 ) / (6 * 12) = + 5^2 / (6 * 6 * 2) = 5^2 / (6^2 * 2).
= (- 5/6)^3 : [+ 25/72] = (- 5^3/ 6^3) : [+ 5^2 /(6^2 * 2)]
= - 5^3 / 6^3 * [ + (6^2 * 2) / 5^2] =
[5^3 si semplifica con 5^2 resta 5^1, 6^3 con 6^2 , rimane 6 al denominatore]:.
= - 5 /6 * (+ 2) = - 5/3.
Ciao @leonardoooooooooo
782)
$\small \dfrac{\left(-\dfrac{3}{2}+\dfrac{2}{3}\right)^3}{-\dfrac{5}{6} : \left(-\dfrac{12}{5}\right)}=$
$\small =\dfrac{\left(\dfrac{-9+4}{6}\right)^3}{-\dfrac{5}{6}·\left(-\dfrac{5}{12}\right)}=$
$\small =\dfrac{\left(-\dfrac{5}{6}\right)^3}{\dfrac{25}{72}}=$
$\small = -\dfrac{125}{216}·\dfrac{72}{25}=$
$\small = -\dfrac{\cancel{125}^5}{\cancel{216}_3}·\dfrac{\cancel{72}^1}{\cancel{25}_1}=$
$\small = -\dfrac{5}{3}·\dfrac{1}{1}=$
$\small = -\dfrac{5}{3}$